1989
DOI: 10.3758/bf03199562
|View full text |Cite
|
Sign up to set email alerts
|

Word attributes and lateralization revisited: Implications for dual coding and discrete versus continuous processing

Abstract: Three attributes of words are their imageability, concreteness, and familiarity. From a literature review and several experiments, I previously concluded (Boles, 1983a) that only familiarity affects the overall near-threshold recognition of words, and that none of the attributes affects right-visual-field superiority for word recognition. Here these conclusions are modified by two experiments demonstrating a critical mediating influence of intentional versus incidental memory instructions. In Experiment 1, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Responses were also more accurate (by 12.13%) in distinguishing low-imagery words from nonwords when they appeared in the RVF. This corresponds with research that has found a RVF advantage for low-imagery words (Boles, 1989;Bruyer & Strypstein, 1985;Bub & Lewine, 1988;Deloche et al, 1987;Marcel & Patterson, 1978;Young & Ellis, 1985). Furthermore, as there is a high correlation between concreteness and imageability (Paivio et al, 1968;Toglia & Battig, 1978), the current results are also consistent with those studies that have found a RVF advantage for abstract words (Bradshaw, 1980;Day, 1977Day, , 1979Ellis & Shepherd, 1974;Ely et al, 1989;Hines, 1976Hines, , 1977Rodel et al, 1983).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Responses were also more accurate (by 12.13%) in distinguishing low-imagery words from nonwords when they appeared in the RVF. This corresponds with research that has found a RVF advantage for low-imagery words (Boles, 1989;Bruyer & Strypstein, 1985;Bub & Lewine, 1988;Deloche et al, 1987;Marcel & Patterson, 1978;Young & Ellis, 1985). Furthermore, as there is a high correlation between concreteness and imageability (Paivio et al, 1968;Toglia & Battig, 1978), the current results are also consistent with those studies that have found a RVF advantage for abstract words (Bradshaw, 1980;Day, 1977Day, , 1979Ellis & Shepherd, 1974;Ely et al, 1989;Hines, 1976Hines, , 1977Rodel et al, 1983).…”
Section: Discussionsupporting
confidence: 93%
“…Confirmation of this suggestion has been found in several studies which have demonstrated that imageability, but not concreteness, influences word recognition in each hemisphere. These studies have indicated that imageability interacts with hemispheric presentation, where the right but not the left hemisphere is selectively disadvantaged in processing low-imagery words (e.g., Boles, 1989;Bruyer & Strypstein, 1985;Marcel & Patterson, 1978;Young & Ellis, 1985). A study by Deloche, Seron, Scius, and Segui (1987) is representative of this group of studies.…”
mentioning
confidence: 93%
“…Pathways most highly upregulated included lysosomal and lytic vacuole membrane roles, suggestive of key CYB561A3 activity within this compartment (Figure 3A-B). The most downregulated genes involved responses to endoplasmic reticulum stress and metal ions, including transcripts encoding the stress response transcription factor ATF5, 40 the cysteine-rich antioxidant protein MT2A (which binds zinc and calcium), 41 and the HSP70 family chaperones HSPA6 and HSPA1B (Figure 3A, C). Several HSP70 family members have key roles in Fe-S cluster biogenesis 42 and assist cellular stress responses.…”
Section: Cyb561a3 Ko Downregulates Metal Ion Response Genes and Cause...mentioning
confidence: 99%
“…The explicit encoding paradigm was chosen, because concrete words are recognized better than abstract words, as predicted by the concreteness effect (Boles, 1989).…”
Section: Introductionmentioning
confidence: 99%